A new genus of aquatic coleopteran from Venezuela (Hydradephaga: Noteridae) (UNED Research Journal, 2018)
Suphisellus is a Nearctic genus of aquatic coleopterans that has been misidentified in the tropics. We analyzed “Suphisellus shorti” from Venezuela and concluded that the identification was based on a misinterpretation of a buccal appendix and two thoracic sclerites. We rename it Llanoterus shorti, a new genus and a new combination, based on gonocoxas, lateroterguites, gonocoxoesternites, pronotum, prosternal process and metaventrites. We illustrate habitus, female and male genitals, and other thoracic sclerites.
Keywords: aquatic coleopteran; new combination; new genus; Noterini; Suphisellus